School-Based Early Detection, Mental Health Education, and Youth Mental Health Cadre Orientation for Adolescents - bunga permata wenny; Rika Sarfika; Feri Fernandes; Randy Refnandes; Dewi Eka Putri; Atih Rahayuningsih; Mahatir; Ira Erwina; Windy freska; Okky Adelirandy; Kiki Hardiansyah Safitri (Warta Pengabdian Andalas, 2026)
Adolescent mental health problems require early identification and school-based follow-up. This community service program aimed to map self-reported symptoms of depression, anxiety, and stress and to deliver mental health education and Youth Mental Health Cadre orientation at SMK N 1 Lembah Gumanti. On May 28, 2025, 225 eleventh-grade students completed the Indonesian Depression Anxiety Stress Scales for Youth (IDASS-Y) and participated in face-to-face education, coping-skill demonstrations, and peer-support orientation. Screening data were analyzed descriptively. Symptoms above the normal category were identified for anxiety in 90 students (40.0%), depression in 56 (24.9%), and stress in 51 (22.7%). Moderate-to-extremely-severe categories were recorded in 54 students (24.0%) for anxiety, 34 (15.1%) for depression, and 28 (12.4%) for stress. The program delivered education and clarified cadres’ roles as peer educators and referral connectors. However, no pre-post assessment measured changes in literacy, stigma, behavior, or cadre competence. The findings support confidential follow-up for students with elevated scores, supervised peer support, and a formal referral pathway linking the school with primary care and mental health professionals. Future programs should include pre-post and follow-up evaluation.